The dyeability of natural dyes from vitex trifolia leaves (daun lemuni) on chitosan-treated cotton fabric / Hani Amirah Abdul Malik - Abdul Malik, Hani Amirah (2014)
This study is would like to discuss about the potential of vitex trifolia leaves to be one of an eco-friendly natural source dye for cotton. Cotton fibre is widely consumed for clothing materials all over the globe. It is chosen due to the softness, versatility, absorbance and breathability. The surface modification of textile fibres is considered as the best route to obtain modern textile treatments. The purpose of this study is to draw some attention on treating the surface of cotton fabric by using chitosan. It is also to investigate the dye ability of vitex trifolia leaves on the treated and untreated cotton fabric based on colour strength analysis, rubbing and crocking fastness testing, colour fastness to perspiration in alkali testing and washing fastness testing. The study has shown that the treated cotton fabric has a better dye ability compared to the untreated fabric. The vitex trifolia leaves have given a brown colour of dye.